Book Review «WTO Law: Theory and Practice of Application» / edited by Doctor of Law, Professor L.P. Anufrieva (M.: Norma-Infra-M., 2016. 528 p.) - A. O. Chetvericov (Московский журнал международного права)
The article (book review) provides the general outline of the book «WTO Law: Theory and Practice of Application» / directed by Doctor of Law, Professor L.P. Anufrieva, published in 2016 by Norma-Infra-M. (hereinafter: book). The book can be considered as a comprehensive legal study providing the most up-to-date and fundamental analysis in the Russian Legal Science of the problematic aspects of functioning of the WTO legal order from the theoretical and practical points of view. The subject-matter of the book embraces all main features of the modern WTO Law such as the role of the WTO in the regulation of international trade (chapter I), WTO Law as a category of the international law science (chapter II), structure and system of the WTO Law (chapter III), the closed treaty regimes and the WTO Law (chapter IV), application of the WTO Law and national legal systems (chapter V), dispute-settlement and implementation of the WTO Dispute-Settlement Body decisions (chapter VI).